The Metal–Support Interaction Concerning the Particle Size Effect of Pd/Al2O3 on Methane Combustion. Issue 50 (15th November 2017) - Murata, Kazumasa; Mahara, Yuji; Ohyama, Junya; Yamamoto, Yuta; Arai, Shigeo; Satsuma, Atsushi
Abstract: The particle size effect of Pd nanoparticles supported on alumina with various crystalline phases on methane combustion was investigated. Pd/θ, α‐Al2 O3 with weak metal‐support interaction showed a volcano‐shaped dependence of the catalytic activity on the size of Pd particles, and the catalytic activity of the strongly interacted Pd/γ‐Al2 O3 increased with the particle size. Based on a structural analysis of Pd nanoparticles using CO adsorption IR spectroscopy and spherical aberration‐corrected scanning/transmission electron microscopy, the dependence of catalytic activity on Pd particle size and the alumina crystalline phase was due to the fraction of step sites on Pd particle surface. The difference in fraction of the step site is derived from the particle shape, which varies not only with Pd particle size but also with the strength of metal–support interaction. Therefore, this interaction perturbs the particle size effect of Pd/Al2 O3 for methane combustion. Abstract : Size and phase matters : Pd/θ‐Al2 O3 and Pd/α‐Al2 O3 exhibit a different size effect from Pd/γ‐Al2 O3 . Based on a structural analysis using spectroscopy and microscopy, the dependence of catalytic activity on size and the alumina crystalline phase was due to the fraction of step sites on the Pd particle. This difference in fraction is derived from the particle shape, which varies with Pd particle size and strength of metal–support interaction.